HRM STRATEGY: PSYCHOEDUCATION TO OVERCOME BURNOUT FOR MSMES IN BUSINESS DEVELOPMENT - Nanang Handoko; Pompong Budi Setiadi, Sri Rahayu (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
In the era of technological progress, various pressure situations and the burden of life responsibilities experienced by MSMEs such as unstable economic conditions, tight business competition against fellow business actors, lack of quality human resource knowledge, difficulty in developing creativity and innovation and other pressures experienced by MSME actors. Thus, MSME actors are very vulnerable to experiencing burnout. Burnout is a form of self-response fatigue in internal or external processes that can lead to a person’s physical and psychological tension. The main aim of this research is for MSME actors to be able to overcome the burnout conditions experienced by providing knowledge about HR management in overcoming stress management is a way of thinking and reacting that is shown to overcome the impacts caused by burnout. This education targets MSME actors in Madiun City. Methods used in In this research, psychoeducational activities involve providing material accompanied by the Box Breathing relaxation technique and providing the Coaching Game Point Of You in the form of several picture cards that can stimulate the subject’s mind. Psychological techniques for effective communication. This psychoeducational activity received a positive response from MSME actors. This psychoeducation activity has benefits for MSME players, such as knowing more clearly about the burnout they experience and how to process burnout well. Based on the implementation of the activities that have been carried out, MSME actors appear to have high enthusiasmBased on observations and interviews, many participants asked questions for consultation and resulted in changes in the atmosphere of MSME players becoming aware of the situation to develop amidst business competition which requires mental health to be productive.